Experience matters: The mediating role of gameful experience in the relationship between gamified competition and perceived innovation culture - Corinna Vera Hedwig Schmidt; Jonas Manske; Tessa Christina Flatten (Creativity and Innovation Management, 2023)
Employees perceiving their organizational culture as innovative increase their output and enhance company performance. A potential approach to improving employees' perception of an innovation culture involves implementing gamified competition in the workplace. Despite the numerous studies on gamified competition, its relationship with employees' perceived innovation culture and the role of their gameful experience remains unclear. On the basis of affordance theory, we explain how gamified competition increases employees' perceived innovation culture (inter-perception) through the mechanism of gameful experiences (intra-perception). We survey a sample of 382 sales employees from German credit institutions who work with a gamified sales application. With the use of structural equation modelling, we find that gamified competition is positively related to perceived innovation culture. However, when including the mediator, results show that employees' gameful experience fully mediates the relationship between gamified competition and perceived innovation culture. Our study underlines the need for research to shift to an experience-oriented employee perspective that will enable a better understanding of the impact a gamified competition has on employees' perceptions. Our findings can help managers to design, predict, and adapt gamified competition in the workplace.
Keywords: 330; gameful experience; gamification; gamified competition; intra- and inter-perception; perceived innovation culture